Risky Decision Making in Juvenile Myoclonic Epilepsy - Unterberger, Iris; Zamarian, Laura; Prieschl, Manuela; Bergmann, Melanie; Walser, Gerald; Luef, Gerhard; Javor, Andrija; Ransmayr, Gerhard; Delazer, Margarete (Frontiers in Neurology, 2018)
It is not known whether patients with Juvenile Myoclonic Epilepsy (JME) differ from healthy people in decision making under risk, i.e. when the decision-making context offers explicit information about options, probabilities, and consequences already from the beginning. In this study, we adopted the Game of Dice Task-Double (GDT-D) to investigate decision making under risk in a group of 36 patients with JME (mean age 25.25/SD 5.29 years) and a group of 38 healthy controls (mean age 26.03/SD 4.84 years). Participants also underwent a comprehensive neuropsychological assessment focused on frontal executive functions. Significant group differences were found in tests of psychomotor speed and divided attention, with the patients scoring lower than the controls. Importantly, patients made risky decisions more frequently than controls. In the patient group, poor decision making was associated with poor executive control, poor response inhibition, and a short interval since the last seizure episode. Executive control and response inhibition could predict 42% of variance in the frequency of risky decisions. This study indicates that patients with JME with poorer executive functions are more likely to make risky decisions than healthy controls. Decision making under risk is of major importance in every-day life, especially with regard to treatment decisions and adherence to long-term medical therapy. Since even a single disadvantageous decision may have long-lasting consequences, this finding is of high relevance.